Uberlândia e a espacialidade festiva : por uma cartografia das festas populares rurais e urbanas - Carvalho, Ana Paula (2022)
The present research is motivated by the binomial celebration and heritage, allied to the geographic perspective of the place. It is linked to PROMEP's research line 1: Culture, preservation and identities, which investigates the plots and forms of identity construction and belonging. Through discursive and visual narratives, we gather important aspects for the understanding of popular festivals in the city of Uberlândia, Minas Gerais, in the spaces where they take place. The object of study considers its urban, poetic and historical symbology, which leads us to see a festive effervescence in the city. The work is conducted through the methodological procedure of documental and bibliographic survey around the main festivities of strong sociocultural impact in the main town and in the districts. After that, as a proposed product for this Professional Master's Degree, it promotes a thematic mapping, based on the cultural cartography approach, using a Geographic Information System (GIS). It starts from the hypothesis that cultural groups - interacting - are the main agents of preservation, inclusive development, sustainability and social strengthening. During the bibliographic and documental survey, the works relevant to the theme were treated according to the sections discussed in the research: cultural heritage; celebration; Uberlândia; carnival; congado; revelry of kings and feasts of saints. In order to reflect about the presence and participation of the geographic perspective in the researches that involve the festivals, the terms map; mapping; cartography and place were searched in the analyzed texts, in order to raise the existence of cartographic, thematic and visual elements in the researches, as well as the treatment of the festive territory as a heritage-place. As a result, the cartography produced demonstrated the cultural resistance of the festivity heritage in the spatial dynamics of Uberlândia. We conclude that the elaboration of a festive cartography supports not only the dialogue among researchers, between researchers and society, but demonstrates that the safeguard of these festivals-patrimony is conducted, in the first place, by the holders of these celebrations.